Effect of fractional crystallization on composition and thermal behavior of coconut oil - Marikkar, Mohammed Nazrim; Saraf, D.; Dzulkifly, M.H. (Taylor and Francis, 2013)
This study was aimed to fractionate coconut oil into its high-and low-melting fractions and determine the composition and thermal property changes. A sample of coconut oil was cooled down in a state of a solution in acetone, and allowed to crystallize isothermally at 10oC for 6 h. When the crystallized component and the mother liquor were isolated and analyzed by using chromatographic techniques, considerable deviations in the fatty acid and triacylglycerol compositions could be noticed with respect to the original sample. Analyses by using differential scanning calorimetry showed that the changes in compositions are found to affect the overall melting behavior of the two fractions. In the high-melting fraction, the onset, and endset were found to have shifted towards the higher temperature region with a concurrent reduction in its melting range. Vice-verse, the onset, and endset of the low-melting fraction has shifted toward the low-temperature region with an increase in its melting range. The reduction of the melting range of the high-melting fraction could make it a specialty fat for applications in confectionery.